New species and records of springsnails (Caenogastropoda: Cochliopidae: Tryonia) from the Chihuahuan Desert (Mexico and United States), an imperiled bio-diversity hotspot - Hershler, Robert; Liu, Hsiu-Ping; Landye, J. Jerry (Zootaxa, 2011)
We describe 13 new, narrowly localized species of the aquatic gastropod genus Tryonia from springs in the Chihuahuan Desert (Chihuahua and Texas): T. allendae n. sp., T. angosturae n. sp., T. chuviscarae n. sp., T. contrerasi n. sp., T. julimesensis n. sp., T. metcalfi n. sp., T. minckleyi n. sp., T. molinae n. sp., T. oasiensis n. sp., T. ovata n. sp., T. peregrina n. sp., T. taylori n. sp. and T. zaragozae n. sp.. These novelties are distinguished by shell and other morphologic characters and are well differentiated genetically from each other and from other congeners (mtCOI sequence divergence >1.9%). We also provide two new records for T. seemani (Frauenfeld, 1863), which is distributed near the southern limit of the Chihuahuan Desert (Durango State) and previously had been thought to be possibly extinct. Bayesian analysis of a mtCOI dataset resolved two clades composed of novelties described herein: one (containing four species) is distributed in several drainages in Chihuahua, the other (containing three species) is a local species flock in the Río Conchos basin (also in Chihuahua) that lives in the warmest waters yet recorded for Tryonia (41–44°C). (The phylogenetic relationships of the other new species were not well supported.) Both of these clades contain sympatric species pairs; co-occurrence of Tryonia congeners previously had been reported only in Ash Meadows (southern Nevada). Some of the species described herein are from previously unsurveyed localities and may help delineate new areas of endemism within the Chihuahuan Desert. One of the new species (T. julimesensis) became extinct between 1991 and 2001 and another (T. oasiensis) disappeared from its single known locality shortly after it was first discovered in 2009 and also may be extinct. The other species treated herein are at risk of extirpation owing to the declining extent and condition of their unprotected habitats.